American Society of Regional Anesthesia and Pain Medicine Local Anesthetic Systemic Toxicity checklist: 2020 version. Issue 1 (4th November 2020) - Neal, Joseph M; Neal, Erin J; Weinberg, Guy L
Abstract : The American Society of Regional Anesthesia and Pain Medicine (ASRA) periodically updates its practice advisories and associated cognitive aids. The 2020 version of the ASRA Local Anesthetic Systemic Toxicity checklist was created in response to user feedback, simulation studies and advances in medical knowledge. This report presents the 2020 version and discusses the rationale for its update.